The Ability Solve Geometry Problems in Spatial Intelligence Through Project Based Learning-Ethnomathematics Assisted by Augmented Reality Apk - Muwahiddah, Ulil; Asikin, Mohammad; Mariani, Scolastika (Unnes Journal of Mathematics Education Research, 2021)
This study aims to find patterns of students' geometry problem-solving abilities after applying learning based on augmented reality-based learning-ethnomatemics apk in terms of spatial intelligence. This study uses a mixed method with explanatory sequential design. The population is students of class VIII Al-Madina Islamic junior high School Semarang 2018/2019 school year. The subjects in this study were students of class VIII selected based on three categories of spatial intelligence, namely high, medium and low. Data collection techniques using tests of students' geometry problem solving abilities, spatial intelligence tests and interviews. The results of this study are learning using project-based learning-ethnomatematics and learning using effective project-based learning-ethnomatatics assisted with augmented reality apk, averaging the three different sample classes, and description of geometry problem solving abilities in terms of students' spatial intelligence in the high, medium, and low categories in project-based learning-ethnomatematics assisted with augmented reality apk obtained the result that the level of spatial intelligence of students may not necessarily describe the level of problem solving ability.